2017
DOI: 10.1186/s40878-017-0062-2
|View full text |Cite
|
Sign up to set email alerts
|

Sampling immigrants in the Netherlands and Germany

Abstract: This paper discusses the limitations of harmonised sampling designs for survey research on immigrants in Germany and the Netherlands. Although the concepts for immigrants are largely similar in both countries, there are severe constraints when it comes to comparable sampling designs. While in the Netherlands a sample can be drawn from a national population register by Statistics Netherlands, this is impossible in Germany due to the decentralised setup of the population register and legal restrictions on mergin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…While Japanese addressing system (Universal Postal Union 2021) differs, for example, greatly from the German one, other countries might not even have fully implemented addressing systems (Universal Postal Union 2012). Finally, and on a minor note, it is worth mentioning that using German population registers for sampling is generally a rather complex exercise binding substantial resources (Salentin and Schmeets 2017); consequently, it might not always be a feasible option for research projects with limited funds. Despite these limitations, GERPS showed that German population registers can, especially with regard to European target countries, be used to achieve high-quality probability-based samples of individuals who registered their emigration with the authorities in recent months prior to the sampling for a given project.…”
Section: Another Origin-based Strategy Has Recently Been Employed By the German Emigration And Remigrationmentioning
confidence: 99%
“…While Japanese addressing system (Universal Postal Union 2021) differs, for example, greatly from the German one, other countries might not even have fully implemented addressing systems (Universal Postal Union 2012). Finally, and on a minor note, it is worth mentioning that using German population registers for sampling is generally a rather complex exercise binding substantial resources (Salentin and Schmeets 2017); consequently, it might not always be a feasible option for research projects with limited funds. Despite these limitations, GERPS showed that German population registers can, especially with regard to European target countries, be used to achieve high-quality probability-based samples of individuals who registered their emigration with the authorities in recent months prior to the sampling for a given project.…”
Section: Another Origin-based Strategy Has Recently Been Employed By the German Emigration And Remigrationmentioning
confidence: 99%
“…In the second stage, target persons are randomly drawn, according to proportional age and sex strata, through the residents registries (Einwohnermeldeämter) within these municipalities. Since Germany has a federal administrative system, in contrast to other European countries, no central residents registry exists [4]. Every municipality therefore needs to be contacted separately.…”
Section: Sampling Strategiesmentioning
confidence: 99%
“…Migration has increased since the Second World War, for several reasons. Whereas the recruitment of migrant "guest workers" in the 1950s, and the resulting family reunifications in the 1970s, and European Union enlargement in the 2000s were primarily work oriented, numerous conflicts and wars have led to an increase of refugees coming to Germany, especially since the 2000s [2][3][4]. The group of PMB in Germany can be described as very heterogeneous, due to differences in the phases of influx, migration background, or specific life circumstances.…”
Section: Introductionmentioning
confidence: 99%
“…I focus on the Netherlands for three reasons. First, the Netherlands is a country with a significant proportion of persons with a migrant background 1 (Salentin and Schmeets 2017) and where immigrants are often considered to hold a disadvantaged position in the housing market (OECD 2015). Second, there is growing evidence that taste-based and statistical discrimination do take place in the Netherlands in the private renting sector but also mong mortgage lenders (Aalbers 2007;Sociaal en Cultureel Planbureau 2009; De Groene Amsterdammer 2018).…”
Section: Introductionmentioning
confidence: 99%